2021
DOI: 10.3390/genes12101552
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Molecular Evaluation: Reporting Three Novel Mutations and Creating Awareness of Pycnodysostosis Disease

Abstract: Pycnodysostosis is a rare autosomal recessive disorder with characteristic diagnostic manifestations. This study aims to phenotype and provide molecular characterization of Egyptian patients, with emphasis on identifying unusual phenotypes and raising awareness about pycnodysostosis with different presentations to avoid a mis- or under-diagnosis and consequent mismanagement. We report on 22 Egyptian pycnodysostosis patients, including 9 new participants, all descending from consanguineous families and their ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 37 publications
1
9
1
Order By: Relevance
“…Additionally, brachydactyly was present in 66.0% of cases, and acroosteolysis was noted in 58.1%. While previous studies 10 13 17 31 50 have identified sleep apnea among characteristics of PYCD, it was not commonly observed in this systematic review, appearing in only 13.5% of the reported cases.…”
Section: Discussioncontrasting
confidence: 78%
See 4 more Smart Citations
“…Additionally, brachydactyly was present in 66.0% of cases, and acroosteolysis was noted in 58.1%. While previous studies 10 13 17 31 50 have identified sleep apnea among characteristics of PYCD, it was not commonly observed in this systematic review, appearing in only 13.5% of the reported cases.…”
Section: Discussioncontrasting
confidence: 78%
“…Based on examination of the full texts of these papers, 84 studies 3 4 5 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations